Microstructure and Mechanical Properties of Polymer-Phosphazene Mortar Exposed to Sulfate Attack - Tanyildizi, Harun (Amer Concrete Inst, 2019)
This study investigated polymer phosphazene mortars subjected to external sulfate attack for 1 year to examine their resistance to the sulfate effect Then, the mechanical properties and microstructure of polymer phosphazene mortars were studied. The number of experiments was reduced by selecting the L-25 orthogonal array. Samples were produced in sizes of 50 x 50 x 50 mm (1.97 x 1.97 x 1.97 in.) and 25 x 25 x 285 mm (0.98 x 0.98 x 11.22 in.). The samples were dried at 105 +/- 5 degrees C (221 +/- 9 degrees F) for 24 hours after curing for 28 days. Later; the monomer containing phosphazene was impregnated to samples at atmospheric conditions for 1 day. The polymerizations of samples were carried out at 60 degrees C (140 degrees F) for 4 hours. These samples were subjected to sulfate attack for 30, 60, 90, 180, and 365 days. The compressive strength, weight, and length changes of polymer-phosphazene mortars subjected to external sulfate attack were determined. After the external sulfate attack, scanning electron microscope (SEM), energy-dispersive X-ray (EDX), and X-ray diffraction (XRD) analyzes of the samples were carried out. The analysis of variance (ANOVA) results showed that the most effective parameter was cement dosage. The results showed that sulfate was prevented from entering into the concrete as cracks and voids in the samples were filled with phosphazene polymers.
Keywords: external sulfate attack; mechanical properties; microstructure; polymer-phosphazene mortars